2014
DOI: 10.1001/jamaneurol.2014.1428
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lifestyle Modifications on Age-Related Free Radical Injury to Brain

Abstract: [2013][2014][2015][2016][2017][2018] seeks to optimize brain health as we age. Free radical injury is an important effector of molecular and cellular stress in the aging brain that derives from multiple sources.OBJECTIVE To identify potentially modifiable risk factors associated with increased markers of brain oxidative stress. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional, academic multicenter study consisted of 320 research volunteers (172 women) aged 21 to 100 years who were medically healthy and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
(34 reference statements)
2
9
0
2
Order By: Relevance
“…We found, consistent with some previous studies (Fukui et al, 2011; Khadir et al, 2015; Peskind et al, 2014; Wiener et al, 2014), that women had higher levels of F2-isoprostanes. Antioxidant effects of estrogen have been demonstrated in cardiovascular and metabolic diseases, which might possibly account for the gender variance (Arias-Loza et al, 2013; Vassalle et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We found, consistent with some previous studies (Fukui et al, 2011; Khadir et al, 2015; Peskind et al, 2014; Wiener et al, 2014), that women had higher levels of F2-isoprostanes. Antioxidant effects of estrogen have been demonstrated in cardiovascular and metabolic diseases, which might possibly account for the gender variance (Arias-Loza et al, 2013; Vassalle et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In the general population, oxidative stress is associated with higher body mass index (BMI) (Keaney et al, 2003; Vincent and Taylor, 2006), cigarette smoking (Bachi et al, 1996; Morrow et al, 1995), alcohol use (Meagher et al, 1999), and cardiovascular and metabolic diseases (Basu, 2008; Davies and Roberts, 2011; Stephens et al, 2009). In some studies, oxidative stress differed between men and women, with greater oxidative stress being found in women (Fukui et al, 2011; Khadir et al, 2015; Peskind et al, 2014; Wiener et al, 2014). Three of these studies found significant gender differences that persisted when controlling for BMI or abdominal adiposity (Fukui et al, 2011; Khadir et al, 2015; Peskind et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We analyzed CSF samples and data from an existing CSF repository from an academic multicenter study. Study procedures pertaining to this repository and multicenter study have been previously described . The sites involved were the University of Washington, University of California, San Diego, Oregon Health and Science University, University of Pennsylvania, Indiana University, and University of California, Davis.…”
Section: Methodsmentioning
confidence: 99%
“…23 A degeneração cerebral presente em idosos ocorre pela diminuição dos campos dendríticos e atrofia principalmente do córtex frontal, 24 que podem estar relacionadas com o acúmulo de alumínio nessa região cortical durante o envelhecimento e consequentes níveis elevados de lipofuscina, que apresenta propriedades citotóxicas, 25 além de diminuição da expressão dos genes das caspases 3 e 9, provavelmente relacionados com a ineficiência da apoptose no SNC e posteriores deformações cerebrais. 24 …”
unclassified